Degrading Sarcasm in Verbal Bullying : A Speech Act Study on Junior High School Students in Surakarta, Indonesia - Maulana Danar Maalikih; Sumarwati Sumarwati; Ani Rakhmawati (Program Studi DIII Rekam Medis dan Informasi Kesehatan, 2024)
Sarcasm is a form of verbal bullying that often occurs unconsciously by the speaker. This study aims to examine the phenomenon of sarcasm-based verbal bullying in the school environment, focusing on degrading speech acts directed at junior high school (SMP) students in Surakarta, Indonesia. Through interviews with students who have been victims of sarcasm, this research analyzes the forms and impacts of sarcastic remarks they have experienced. The findings reveal that sarcasm is frequently used as a form of mockery or insult aimed at highlighting the victim’s shortcomings, whether in academic, physical, or social aspects. Each sarcastic utterance is analyzed using the theories of locution, illocution, and perlocution, showing that while the utterance may appear as a compliment on a literal level, it contextually demeans the victim. The perlocutionary effect includes feelings of shame, inferiority, and loss of self-confidence in the victim. These findings indicate that sarcasm as verbal bullying has the potential to damage students’ mental health and disrupt their social relationships. This study emphasizes the need for a school environment that supports positive communication, free from speech acts that have the potential to demean others.